1984
DOI: 10.7164/antibiotics.37.836
|View full text |Cite
|
Sign up to set email alerts
|

Griseochelin, a novel carboxylic acid antibiotic from Streptomyces griseus.

Abstract: Griseochelin, C3,H;;QO" isolated from an asporogenous strain of Streptonryces griseus represents a novel carboxylic acid antibiotic. The metabolite, which is active against Grarnpositive bacteria, forms water-insoluble salts with mono-and divalent cations and binds alkaline-earth metal ions specifically in 2: 1 (X_M) stoichiometry.Detailed spectral (IR, MS and NMR) studies provide full characterization of its constitution featuring a carboxylic acid function, a substituted tetrahydropyran ring, an allylic OH g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 10 publications
0
22
0
2
Order By: Relevance
“…) 1d. Typical methods to construct these types of substituted frameworks use nucleophilic‐substitution reactions at the anomeric position (2‐position) of THP ethers or esters.…”
Section: Introductionmentioning
confidence: 99%
“…) 1d. Typical methods to construct these types of substituted frameworks use nucleophilic‐substitution reactions at the anomeric position (2‐position) of THP ethers or esters.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] Zincophorin weist potente Aktivitätg egen Grampositive Bakterien einschließlich dem hçchst pathogenen Clostridium coelchii auf; [38,40] das Methylester-Derivat zeigt antivirale Aktivitätm itsamt reduzierter Toxizität. [38][39][40] Zincophorin weist potente Aktivitätg egen Grampositive Bakterien einschließlich dem hçchst pathogenen Clostridium coelchii auf; [38,40] das Methylester-Derivat zeigt antivirale Aktivitätm itsamt reduzierter Toxizität.…”
Section: Zincophorinunclassified
“…Zincophorin Zincophorin (3)-das früher Griseochelin genannt wurde, wobei der aktuelle Name durch die hohe Affinitätd es Moleküls zu Zink-Kationen zustande kommt -w urde 1984 aus Streptomyces griseus isoliert und die Struktur wurde zweifelsfrei über 2D-NMR-und XRD-Untersuchungen aufgeklärt. [38][39][40] Zincophorin weist potente Aktivitätg egen Grampositive Bakterien einschließlich dem hçchst pathogenen Clostridium coelchii auf; [38,40] das Methylester-Derivat zeigt antivirale Aktivitätm itsamt reduzierter Toxizität. [41] Diese potente Aktivitätm acht sowohl Zincophorin als auch den Methylester 4 zu attraktiven Zielmolekülen.…”
Section: Aktuelle Fortschritte In Der Synthese Von Polyether-ionophorunclassified
“…In 1984, Gräfe et al reported the isolation of a new mono-carboxylic acid ionophore, griseocholin, from cultured strains of Streptomyces griseus 2. The structure was established first by extensive NMR experiments 3.…”
Section: Introductionmentioning
confidence: 99%